Phytochemical profile and allelopathic potential of Haloxylon scoparium Pomel (Chenopodiaceae) from Algerian Sahara - Reguia OTMANI; Bachir KHENE; Abdellah KEMASSI; Fatna ARABA; Mohamed HARRAT; Mohamed YOUSFI (Acta Agriculturae Slovenica)
The aim of the present work is to study the chemical composition, to estimate the phenolic compounds content and to evaluate the potential allelopathic effects of the Haloxylon scoparium Pomel. Phytochemical tests revealed that Haloxylon scoparium contains tannins, saponins, coumarins, alkaloids, flavonoids and steroids. Furthermore, it contains high levels of total phenolic (588.33 mg GAE 100 g-1) and flavonoids (95.45 mg QE 100 g-1) contents. Moreover, LC-MS-MS analysis allowed us to determine their chemical composition. The results of this characterization confirm the presence of vanillin, naringenin, folic acid, maleic acid, benzoic acid, myricetin, qwuercetin, beta-carotene, butylhydroxyanisole (BHA), butylated hydroxytoluene (BHT), rutin, cafeic acid, hydroxy-4-coumarine, ascorbic acid, and gallic acid. The allelopathic effect was studied on seed germination and seedling growth of four weed species. The bioassays were performed using different concentrations (1 %, 2.5 %, 5 % and 10 %) against a negative control. The seed germination, shoot and root length of weed species were completely inhibited at the highest concentrations (10 %, 5 %). However, the lower concentrations exhibited lesser inhibition percentages on the germination and the seedling growth. The phytochemical results and the significant allelopathic effects of the plant extract suggest that this species may offer new substances for the biocontrol of weeds.